Easier without algebra

Algebra Level 1

If x y = x y x - y = xy and 1 x + 1 y = 5 \dfrac{1}{x} + \dfrac{1}{y} = 5 , then what is 1 y \dfrac{1}{y} ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

As x , y 0 x,y \ne 0 , divide the first equation through by x y xy to find that 1 y 1 x = 1 \dfrac{1}{y} - \dfrac{1}{x} = 1 . Add this to the second equation to find that

( 1 y 1 x ) + ( 1 x + 1 y ) = 1 + 5 2 y = 6 1 y = 3 \left(\dfrac{1}{y} - \dfrac{1}{x}\right) + \left(\dfrac{1}{x} + \dfrac{1}{y}\right) = 1 + 5 \Longrightarrow \dfrac{2}{y} = 6 \Longrightarrow \dfrac{1}{y} = \boxed{3} .

Nice - I thought the symmetry of this problem might generate some elegant solutions. Well done!

TJ Evert - 2 years, 7 months ago
Tj Evert
Oct 17, 2018

Given

1) x y = x y x - y = xy

2) 1 / x + 1 / y = 5 1/x + 1/y = 5

From 2),

( x + y ) / x y = 5 (x + y)/xy = 5

with 1)

x + y = 5 x y = 5 ( x y ) = 5 x 5 y x + y = 5xy = 5(x - y) = 5x - 5y

6 y = 4 x 6y = 4x

y = 2 x / 3 y = 2x/3

Substituting into 1)

x ( 2 x / 3 ) = x ( 2 x / 3 ) x - (2x/3) = x(2x/3)

Since x \neq 0,

1 2 / 3 = 2 x / 3 1 - 2/3 = 2x/3

3 2 = 2 x 3 - 2 = 2x

x = 1 / 2 x = 1/2

y = 2 ( 1 / 2 ) / 3 = 1 / 3 y = 2(1/2)/3 = 1/3

1 / y = 3 1/y = 3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...